Stress-induced extracellular vesicle and cytoophidium biology in breast cancer - Kassim, H (2019)
Cells respond to metabolic stresses by reprogramming gene expression, degrading unneeded proteins and altering post-translational modifications of other proteins. Herein, I reported that breast cancer (BC) cells can adapt to cellular stress by modulating the protein composition and function of extracellular vesicles (EVs) and reorganizing metabolic enzymes into filamentous structures, termed cytoophidia. Glutamine is a non-essential amino acid that activates the mechanistic target of rapamycin complex 1 (mTORC1) pathway. I confirmed that luminal and basal lineages of BC cells differ in their glutamine dependencies, and that EVs may mediate intercellular glutamine symbiosis between the two cell lineages (Chapter 3). Despite the difference in sensitivity towards INK128 (an mTOR kinase inhibitor) between lung and brain metastatic clones of basal BC cells, I demonstrated that, blocking mTOR led to secretion of EVs containing proteins associated with cell migration and activation of epithelial-mesenchymal transition (EMT) (Chapter 4). I further demonstrated that the glutamine dependency was not only variable across BC subtypes but also between lung and brain metastatic clones of basal BC cells. Furthermore, my data shows that inhibition of glutamine consumption by 6-Diazo-5-oxo-L-norleucine (DON) significantly promoted higher abundance and length of glutamine-dependent cytidine triphosphate synthase 1 (CTPS1) and inosine-5’-monophosphate dehydrogenase 1 (IMPDH1) cytoophidia in brain metastatic than lung metastatic clone of basal BC cells, highlighting the variation in glutamine dependency across different metastatic clones of basal BC (Chapter 5). The assemblies of cytoophidia of CTPS and many other metabolic enzymes is a stress adaptation strategy to maintain metabolic homeostasis during nutrient starvation, as I demonstrated by conducting a genetic screen in budding yeast (Chapter 5). In summary, my work suggests that stress-induced alteration of protein composition and function of EVs and reorganization of metabolic enzymes into cytoophidia are strategies for BC cell survival in hostile microenvironment.